Static Analyser for Java-Based Object-Oriented Software Metrics - Abu Al-Ese, Hasan Mugbil Khalaf (1999)
Software metrics play a major role In the software development. Not only software metrics help in understanding the size and complexity of software systems, but they are also helpful in improving the quality of software systems. For object-oriented systems, a large number of metrics have been established. These metrics should be supported by automated collection tools. Automated tools are useful for measuring and improving the quality of software systems. One such tool is a static analyser. A static analyser has been developed for a subset of Java language. A number of object-oriented software metrics has been evaluated using attribute grammar approach. Attribute grammar approach is considered as a well-defined approach to the software metrics evaluation since it is based on the measurement of the source code itself. New definitions for a number of object-oriented metrics have been specified using attribute grammars. This tool has been built using C language. Lexical analyser and syntax analyser have been generated using lex and yacc tools under linux operating system. Four object-oriented metrics have been evaluated. These metrics are Depth of Inheritance Tree metric, Number of Children metric, Response For a Class metric, and Coupling Between Object Classes metric. The software metrics will be produced in the common metrics format that is used in SCOPE project.